2015
DOI: 10.1016/j.cell.2014.11.041
|View full text |Cite
|
Sign up to set email alerts
|

Low Affinity Binding Site Clusters Confer Hox Specificity and Regulatory Robustness

Abstract: Summary In animals, Hox transcription factors define regional identity in distinct anatomical domains. How Hox genes encode this specificity is a paradox, because different Hox proteins bind with high affinity in vitro to similar DNA sequences. Here, we demonstrate that the Hox protein Ultrabithorax (Ubx) in complex with its cofactor Extradenticle (Exd) bound specifically to clusters of very low affinity sites in enhancers of the shavenbaby gene of Drosophila. These low affinity sites conferred specificity for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

32
402
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(453 citation statements)
references
References 74 publications
32
402
4
2
Order By: Relevance
“…Therefore, it remains a challenge to determine which of the identified sites are functional. While it has been demonstrated that low-occupancy regions are less likely to contain regulatory information as compared to highoccupancy regions, there are multiple examples of low affinity binding sites driving specific gene expression (Fisher et al 2012;Ramos and Barolo 2013;Crocker et al 2015). Furthermore, binding events that are temporally dynamic over development are enriched for functional binding events, and are more predictive of activity (Jakobsen et al 2007;Li et al 2008Li et al , 2011Zinzen et al 2009;Wilczynski and Furlong 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it remains a challenge to determine which of the identified sites are functional. While it has been demonstrated that low-occupancy regions are less likely to contain regulatory information as compared to highoccupancy regions, there are multiple examples of low affinity binding sites driving specific gene expression (Fisher et al 2012;Ramos and Barolo 2013;Crocker et al 2015). Furthermore, binding events that are temporally dynamic over development are enriched for functional binding events, and are more predictive of activity (Jakobsen et al 2007;Li et al 2008Li et al , 2011Zinzen et al 2009;Wilczynski and Furlong 2010).…”
Section: Discussionmentioning
confidence: 99%
“…6B). Evolutionarily conserved Hox transcription factors were recently found to rely on clustered low-affinity sites to regulate key developmental genes in Drosophila (46). In this respect, polyamides behave like natural transcription factors when binding genomic loci.…”
Section: Discussionmentioning
confidence: 99%
“…Similar analyses with transcription factors show limited success, primarily because most transcription factors are dependent on chromatin accessibility (44). Although commonly used bioinformatic methods annotate genomic regions using only the highest affinity consensus sites (45), DNA-binding proteins in cooperative complexes bind weak-and moderate-affinity binding sites that are typically not considered in modeling genomic occupancy profiles (31,46). Consequently, most computational models predict genome-wide binding patterns of natural transcription factors with varying success (47).…”
Section: Genome-wide Polyamide Distributions In Cells Coincide With Cmentioning
confidence: 99%
“…83 Low affinity binding sites may be lost as they often do not pass the threshold. As it was 84 shown that low-affinity binding is essential in biology [12,59] [55].…”
mentioning
confidence: 99%
“…Incorporating these biologically important binding events [12,59] seems to be relevant 490 for improving the predictions.…”
mentioning
confidence: 99%